Air quality spatial distribution analysis : particulate matter exposure inequality in Bogotá, Colombia (2019)
Air pollution exposure (specially to particulate matter) is nowadays one of the main global health issues. Air quality indexes are measured around the world in order to provide governments useful information that supports decision making. However, these indexes ignore key social-economic information about population that, if were included, could lead to evidence air pollution exposure inequality around the world. In his work, a spatial interpolation methodology known as Kriging is applied using as input the particulate matter information collected in Bogotá, Colombia. These results are then compared to multiple sources information provided by the local government in order to have a better understanding of the city's air pollution and its relationship with the main social-economic variables.